2004
DOI: 10.1079/nrr200482
|View full text |Cite
|
Sign up to set email alerts
|

Wine polyphenols and promotion of cardiac health

Abstract: Wine polyphenols are considered to have beneficial effects on CHD and atherosclerosis. The consumption of red wine is high in Italy and France, approximately four times greater than that in the UK. This disparity in red wine consumption is thought to be the reason for the 'French paradox', where France was shown to have a coronary mortality rate close to that of China or Japan despite saturated fat intakes and cholesterol levels similar to the UK and USA. In the present review, we discuss the effects of wine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 129 publications
(141 reference statements)
0
32
0
1
Order By: Relevance
“…Wine consumption reduces the susceptibility of LDL to oxidation which is important for the prevention of arteriosclerosis development. A moderate wine consumption also increases serum antioxidant capacity (Cooper et al 2004). A favourable influence on the reduction of cancer incidence and on chronic inflammatory diseases, the development of both being associated with oxygen free radical, is probable as well (Scalbert et al 2005).…”
mentioning
confidence: 98%
“…Wine consumption reduces the susceptibility of LDL to oxidation which is important for the prevention of arteriosclerosis development. A moderate wine consumption also increases serum antioxidant capacity (Cooper et al 2004). A favourable influence on the reduction of cancer incidence and on chronic inflammatory diseases, the development of both being associated with oxygen free radical, is probable as well (Scalbert et al 2005).…”
mentioning
confidence: 98%
“…These compounds have earned a reputation for their activity in plants, in defense against insect attacks and in microbial diseases. It is believed that procyanidins can protect from cardiovascular diseases [18,19]. Pinus bark has shown to have antioxidant, anticarcinogenic, antimutagenic, antimicrobial, antiinflammatory, and cardio-cerebrovascular protective effects, among others [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…(Cooper et al, 2004;Opie  Lecour, 2007). The most intriguing are the studies which reported the possible association between red wine consumption and decrease in risk, and some suppression and inhibition of cancers (Briviba et al, 2002).…”
Section: Introductionmentioning
confidence: 99%